Enantioselective Bromination of Silyl Enol Ethers with Chiral Pentacarboxycyclopentadienyl Bromide - Liu, Guo; Li, Pingfan (Synlett, 2023)
Chiral pentacarboxycyclopentadienyl bromide reagents were synthesized to accomplish enantioselective bromination of silyl enol ethers to give corresponding α-bromoketone products in good yields and up to 77% ee. A catalytic version of this reaction was also demonstrated through the combination of Lewis acid activators and diethyl 2,2-dibromomalonate as stoichiometric achiral bromine source.
Keywords: enantioselectivity; asymmetric synthesis; bromine; silyl enol ethers; α-bromoketones; chiral pentacarboxycyclopentadienyl bromide